It takes two to tango: Examining productive interactions in urban research collaboration - Kalliomäki Helka; Ruoppila Sampo; Airaksinen Jenni (Oxford University Press, 2022)
The science–society relations of social sciences and humanities have been increasingly discussed under the concept of productive interactions, which refers to the mutual learning processes between researchers and stakeholders for the benefit of societal development. While most studies have analysed the societal impact from the research performers’ perspective, in this article, we examine the practitioners’ side. We contribute to the evaluation theory by offering a new perspective to examine the emergence of productive interactions. Based on an empirical analysis of collaborative practices in two Finnish urban research programmes and how the practitioners reflected on them, we argue that practitioners’ competencies are essential in leveraging societal impact. The improvement of these ‘pracademic competencies’ need to be raised as an issue in research policy and evaluation promoting responsible research and innovation.